Breastfeeding and the developmental origins of mucosal immunity: how human milk shapes the innate and adaptive mucosal immune systems. Issue 6 (November 2021) - Dawod, Bassel; Marshall, Jean S.; Azad, Meghan B.
Abstract : Purpose of review: Breastfeeding provides passive immunity while the neonatal immune system matures, and may also protect against chronic immune-mediated conditions long after weaning. This review summarizes current knowledge and new discoveries about human milk and mucosal immunity. Recent findings: New data suggest that certain microbes in maternal milk may seed and shape the infant gut microbiota, which play a key role in regulating gut barrier integrity and training the developing immune system. Human milk oligosaccharides, best known for their prebiotic functions, have now been shown to directly modulate gene expression in mast and goblet cells in the gastrointestinal tract. Epidemiologic data show a reduced risk of peanut sensitization among infants breastfed by peanut-consuming mothers, suggesting a role for milk-borne food antigens in tolerance development. Cross-fostering experiments in mice suggest the soluble Toll-like receptor 2, found in human milk, may be critical in this process. Finally, interest in human milk antibodies surged during the pandemic with the identification of neutralizing severe acute respiratory syndrome coronavirus 2 antibodies in maternal milk following both natural infection and vaccination. Summary: Human milk provides critical immune protection and stimulation to breastfed infants. Understanding the underlying mechanisms could identify new therapeutic targets and strategies for disease prevention across the lifespan.